Sampling Species Diversity in a Malaysian Rain Forest: The Case of a Logged-Over Forest - Ibrahim, Faridah Hanum; Philip, L.; Abd. Ghani, Awang Noor (2008)
This study was carried out in a logged-over forest at Compartment 14, Ayer Hitam Forest, Puchong, on a randomly chosen 5-ha area (200mx250m). The 5-ha plot contained a total of 6621 trees (for trees greater than 5cm dbh) which belonged to 319 species in 148 genera and 51 families and that is 11% species, 28% genera and 51% families of the total tree taxa found in Peninsular Malaysia. Endemism and new records were high, 33 species and 30 species respectively. A minimum contiguous area of 5-ha plot is recommended to capture species diversity in a tropical logged-over forest. The implications of the findings are herein discussed within the context of sample plot size, species diversity and conservation of logged-over forest.